(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
This study evaluated the influence of auto-mechanic workshops on the physicochemical properties, heavy metal levels, and pollution status of adjacent farmland soils in Anyigba, Kogi State. Soil pH ranged from 5.2– 6.5, reflecting slight acidification relative to the control (6.8). Electrical conductivity increased to 0.45–1.12 dS/m compared to 0.37 dS/m in the control. Soil organic carbon declined to 0.67–1.83% compared with control’s 3.24%, while cation exchange capacity decreased to 4.56–10.38 cmol/kg compared with 16.83 cmol/kg in the control, indicating reduced nutrient retention capacity. Heavy metal concentrations were markedly elevated, reaching 18.97 mg/kg (Pb), 11.09 mg/kg (Cu), 11.22 mg/kg (Ni), 12.16 mg/kg (Cr), and 2.87 mg/kg (Cd), exceeding control values of 0.83, 1.66, 3.58, 4.76, and 0.27 mg/kg, respectively. Contamination factors (CF) indicated high contamination for Pb (3.95–22.86), Cd (4.37–10.63), and Cu (3.05–6.68), and moderate contamination for Ni (1.93–3.13) and Cr (1.39–2.55). Enrichment factors (EF) showed minimal enrichment for Ni (0.88–1.93) and moderate to significant enrichment for Cd (2.16–5.13), Cu (1.26–3.22), and Pb (2.52–11.00). The Nemerow Pollution Index (3.67–17.77) classified the soils as heavily polluted. The Potential Ecological Risk Index (179.23–480.39) indicated moderate to considerable ecological risk, largely driven by Cd and Pb. Overall, the findings confirm substantial anthropogenic metal inputs from auto-mechanic activities and underscore the need for improved waste management, routine monitoring, phytoremediation strategies, and strengthened regulatory enforcement to prevent food chain contamination.